Pengaruh Latihan Small Sided Games Terhadap Hasil Ketepatan Passing Bawah Menggunakan Kaki Bagian Dalam Sepak Bola SSB MEGAS II BANYUASIN - Gilang Maekhendra; Giartama; Herri Yusfi (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2022)
The purpose of conducting a study was to determine the effect of Small-Sided Games training on the accuracy of lower passing using the inner foot of soccer at SSB Megas II Banyuasin. The research method used is the Experiment one group pretest and posttest method. The research design used is one group pretest-posttest design. Using the total sampling technique to take a sample of 40 people. The research instrument in this study was a modified test of soccer passing accuracy. From the results of data analysis processing through the calculation of the t-test formula with the criteria tcount (11.504) > Ttable (2.002) with a confidence level of 0.95 or 95% (α = 0.05) and the number of samples (N = 40). Submitted accepted. The practice of Small-Sided Games using the inside of the foot affects the accuracy of the bottom passing. Based on the results of research on the effect of Small-Sided Games using the inside of the foot, it turned out to have a significant effect on the accuracy of lower passing at SSB Megas II Banyuasin. This research implies that Small-Sided Games using the inside of the foot can be carried out and used as an exercise program to increase the accuracy of lower passing.